2022
DOI: 10.1002/fsn3.3186
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gamma irradiation and storage condition for improving mechanical and physical postharvest characteristics of fresh garlic cloves

Abstract: Preservation of garlic as an export basic crop for a long time is very important. Garlic is rich in folic acid, vitamin C, calcium, iron, magnesium, potassium, zinc, and vitamins B 2 , B 1 , and B 3 (Balmori et al., 2019;Eugster et al., 2018). It is necessary to maintain the quality of this type of food that is rich in nutrients for a long time (Noda et al., 2018). In order to preserve foods, there are different ways, such as thermal, freezing, drying, fermentation, coating, packaging film, irradiation, atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, the poor hygienic quality of some locally produced foods has led to frequent outbreaks of food‐borne diseases, posing serious threats to public health and life safety. Food irradiation has proven to be a safe and efficient method to extend the shelf life of food, reduce spoilage, eliminate pests, and inactivate bacteria that cause food poisoning (Shi et al, 2020 ; Yoosefian et al, 2022 ). Many international organizations, such as the International Atomic Energy Agency (IAEA), Food and Agriculture Organization (FAO), the World Health Organization (WHO), and the Scientific Committee on Food of the European Commission, have concluded that food irradiated with suitable technologies is very safe and nutritionally acceptable (Arshad et al, 2020 ; Farkas & Mohácsi‐Farkas, 2011 ; Shahi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the poor hygienic quality of some locally produced foods has led to frequent outbreaks of food‐borne diseases, posing serious threats to public health and life safety. Food irradiation has proven to be a safe and efficient method to extend the shelf life of food, reduce spoilage, eliminate pests, and inactivate bacteria that cause food poisoning (Shi et al, 2020 ; Yoosefian et al, 2022 ). Many international organizations, such as the International Atomic Energy Agency (IAEA), Food and Agriculture Organization (FAO), the World Health Organization (WHO), and the Scientific Committee on Food of the European Commission, have concluded that food irradiated with suitable technologies is very safe and nutritionally acceptable (Arshad et al, 2020 ; Farkas & Mohácsi‐Farkas, 2011 ; Shahi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%